2012
DOI: 10.1097/qai.0b013e318269c414
|View full text |Cite
|
Sign up to set email alerts
|

Disease Progression in HIV-1–Infected Viremic Controllers

Abstract: Our data are consistent with a relationship between CD4 T-cell activation and disease progression. HIV-1 DNA load may be a better marker of viral replication and disease progression than viral RNA load. Lower level CD8 T-cell activation correlates with low viral RNA load but not with disease progression or viral DNA load.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 46 publications
4
26
0
1
Order By: Relevance
“…These results are consistent with previous studies, which reported that the majority of circulating CD8 + T cells in individuals with chronic HIV-1 infection were mature effector and effector memory CD8 + T cells (23,24). However, in a cross sectional study by Groves et al (19), discord controllers and typical controllers had higher numbers of naive CD8 + T cells and reduced CD8 + T cell activation, compared with the patients with rapidly progressing disease. Notably, Groves et al defined discord controllers as patients with a viral RNA load <2,000 copies/ml and <450 CD4 + T cells/mm 3 , with the viral load of discord controllers ranging between 100.3 and 1,043.0 copies/ml.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These results are consistent with previous studies, which reported that the majority of circulating CD8 + T cells in individuals with chronic HIV-1 infection were mature effector and effector memory CD8 + T cells (23,24). However, in a cross sectional study by Groves et al (19), discord controllers and typical controllers had higher numbers of naive CD8 + T cells and reduced CD8 + T cell activation, compared with the patients with rapidly progressing disease. Notably, Groves et al defined discord controllers as patients with a viral RNA load <2,000 copies/ml and <450 CD4 + T cells/mm 3 , with the viral load of discord controllers ranging between 100.3 and 1,043.0 copies/ml.…”
Section: Discussionsupporting
confidence: 92%
“…HIV-1. Based on the expression of CD45RA and CD62L, human CD8 + T cells can be divided into four subsets with distinct homing and functional properties: Naïve (CD45RA + CD62L + ), central memory (CD45RA -CD62L + ), effector memory (CD45RA -CD62L -) and effector (CD45RA + CD62L -) cells (18,19). In the present study, the CD8 + T cell subsets were determined in patients with HIV-1.…”
Section: Subsets Of Circulating Cd8 + T Cells Are Altered In Patientsmentioning
confidence: 93%
“…Terminology then changed to refer to such atypical HIV-1 + individuals as “Elite controllers,” “Elite suppressors,” and “HIV controllers” (Deeks and Walker, 2007; Blankson, 2010; Migueles and Connors, 2010). More recently, an additional group of individuals exhibiting a disparate course of clinical disease have been described and termed “Discord controllers” (Groves et al, 2012). These individuals control viral replication to BLD of the routinely available viral load assay, but demonstrate peripheral blood CD4 T-cell counts lower than the normal range, therefore failing to meet the inclusion criteria for LTNP status.…”
Section: The Long-term Non-progressor: Criteria Of Definition and Emumentioning
confidence: 99%
“…More recently, Groves et al [ 16 ▪▪ ] identified ART-naive patients who had maintained a viral load less than 2000 copies/ml for more than 12 months. Typical controllers had an average recent CD4 cell count more than 450 cells/μl (2.1% of population), whereas discord controllers had an average recent CD4 cell count less than 450 cells/μl (0.6%).…”
Section: Long-term Nonprogressors and Elite Controllersmentioning
confidence: 99%
“…As the two groups of individuals appear to be clinically distinct, suggesting differences in the processes that lead to long-term nonprogression and elite control, several research groups have attempted to investigate whether there are any demographic or biological differences between these two patient groups [ 4 ]. Groves et al [ 16 ▪▪ ] reported a more marked depletion of the naive T-cell subset in discord controllers than in typical controllers but a trend towards increased activated effector memory CD4 cells in typical controllers. CD8 T-cell activation was increased to a similar level (compared with noncontrollers) in both controller groups.…”
Section: Long-term Nonprogressors and Elite Controllersmentioning
confidence: 99%